A Prospective Randomized Controlled Trial Comparing Night Splinting with No Splinting after Treatment of Mallet Finger. (June 2014) - Gruber, Jillian S.; Bot, Arjan G. J.; Ring, David
Background: The effectiveness of night splinting after treatment of mallet finger is unknown. We tested the hypothesis that there is no difference in extensor lag between patients with mallet finger that wear a night splint for an additional month after 6 to 8 weeks of continuous splinting and patients that do not wear a night splint. Methods: Fifty-one patients were enrolled in this randomized controlled trial. At enrollment, range of motion was measured for the injured and contralateral uninjured finger. The follow-up was conducted approximately 4 weeks later in person (41 patients) or by phone (10 patients). Analysis was by intention to treat. Results: There were no significant differences in final extensor lag between patients that did and did not receive a night splint. Among the 41 patients with a final in-person evaluation, the final average extensor lag was 14°, and 34 % (14 of 41 patients) had a lag of 20° or greater. Final extensor lag correlated significantly with age, enrollment distal interphalangeal joint (DIP) flexion and extensor lag, and final DIP flexion, with the latter two accounting for 28 % of the variation in final lag in the final multivariable model ( p <0.001). There were no differences in disability ( p =0.67) or treatment satisfaction ( p =0.48) between patients that did and did not use night splints. Conclusions: Supplemental night splinting does not improve the outcome of mallet finger in terms of extensor lag, disability, or satisfaction with treatment. Patients with worse initial extensor lags should expect worse final lags; residual lags of 20° or greater are commonplace.